2021
DOI: 10.4236/cc.2021.94012
|View full text |Cite
|
Sign up to set email alerts
|

A Quantum Chemical Screening of Two Imidazole-Chalcone Hybrid Ligands and Their Pd, Pt and Zn Complexes for Charge Transport and Nonlinear Optical (NLO) Properties: A DFT Study

Abstract: A quantum chemical screening of two imidazole-based chalcone ligands: 2-[1-(3-(1H-imidazol-1-yl)propylimino)-3-(phenylallyl)]phenol and 2-[1-(3-(1Himidazol-1-yl)propylimino)-3-4-nitrophenylallyl]phenol (hereinafter referred to as HL1 and HL2 respectively) and their Pd, Pt and Zn chelates for charge transport and nonlinear optical (NLO) properties, is reported via dispersioncorrected density functional theory (DFT-D3) and time-dependent DFT (TD-DFT) methods. From our results, Pd and Pt complexes have been obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Small reorganization (λ electron/hole ) energy values indicate better charge transport rates and mobility, which give rise to good charge transport properties for the materials [39]. Results from Table 2 show that the increasing trend in the λ electron values is as follows: A smaller IP a value means easier hole injection ability for the OLED materials, while a larger EA a value facilitates electron injection [8,53]. Table 2 shows that INH13 (7.129 eV) has the lowest IP a value, while INH8 (1.578 eV) has the highest EA a value.…”
Section: Reorganization Energies Presented In Tablementioning
confidence: 98%
See 2 more Smart Citations
“…Small reorganization (λ electron/hole ) energy values indicate better charge transport rates and mobility, which give rise to good charge transport properties for the materials [39]. Results from Table 2 show that the increasing trend in the λ electron values is as follows: A smaller IP a value means easier hole injection ability for the OLED materials, while a larger EA a value facilitates electron injection [8,53]. Table 2 shows that INH13 (7.129 eV) has the lowest IP a value, while INH8 (1.578 eV) has the highest EA a value.…”
Section: Reorganization Energies Presented In Tablementioning
confidence: 98%
“…Reorganization energy is partitioned into internal and external reorganization energies [8]. Te internal reorganization energy refers to the energy change of the system caused by the structural relaxation after the gain or loss of electrons, while the external reorganization energy describes the change in electronic polarization of the surrounding compounds [38,39].…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the analysis of the charge transfer in the three structures seems to be essential. In literature, frontier molecular orbitals (FMOs) and natural transitions orbitals (NTOs) have been employed to study and visualize the ICT [34–36] . Even some studies have shown a correlation between the HOMO‐LUMO gap and hyperpolarizabilities and ICT [36–38] …”
Section: Resultsmentioning
confidence: 99%
“…In literature, frontier molecular orbitals (FMOs) and natural transitions orbitals (NTOs) have been employed to study and visualize the ICT. [34][35][36] Even some studies have shown a correlation between the HOMO-LUMO gap and hyperpolarizabilities and ICT. [36][37][38] Frontier molecular orbitals and HOMO-LUMO gap for the three conformers were collected in the Supporting Information and NTOs for the first and second dominant electronic transitions were visualized at the CAM-B3LYP/6-31G(d,p) (Figure 5).…”
Section: Resultsmentioning
confidence: 99%